Pengaturan Organ Komisaris Dalam Perseroan Terbatas Perseorangan Menurut Perspektif Undang-Undang Cipta Kerja - Sudjateruna, Yanuar Agung; Swardhana, Gde Made (Acta Comitas : Jurnal Hukum Kenotariatan, 2021)
Abstract   The purpose of this study is to examine the unregulated Organs of Commissioners in Individual Limited Liability Companies in the Job Creation Act, and to examine the organs authorized to take over the duties and responsibilities of the organs of Commissioners in Individual Limited Liability Companies according to the Job Creation Act. This research is classified as a normative juridical research that uses 3 types of approaches, including the statutory approach, legal interpretation and analysis of legal concepts. The results of the study indicate that the existence of a Commissioner in a Limited Liability Company is not regulated in the work copyright law to avoid a conflict of authority between the Commissioner and the Director who is also the sole shareholder. It is impossible for the supervisory process to be carried out by the Commissioner against the board of directors as well as the sole shareholder who has absolute power. Meanwhile, those who are then authorized to take over the duties and responsibilities of the organs of the Commissioner in an Individual Limited Liability Company are the shareholders, because there is only one personal figure in Individual Limited Liability Companies, namely the Sole Shareholders, who concurrently serves as Director. The organs of  Commissioners in a private company must be regulated and still exist, although in the process of implementation its function is only as a complement, but the void of norms can be avoided. Further regulation is needed to create legal harmonization in order to ensure legal certainty.   Abstrak   T ujuan dari penelitian ini adalah untuk mengkaji tidak diaturnya Organ Komisaris dalam Perseroan Terbatas  Perseorangan dalam Undang-undang  Cipta Kerja, dan mengkaji organ yang berwenang untuk mengambil alih tugas dan tanggungjawab organ Komisaris dalam Perseroan Terbatas Perseorangan menurut Undang-undang Cipta Kerja.  Penelitian ini tergolong jenis penelitian yuridis normatif  yang menggunakan 3 jenis pendekatan, antara lain p endekatan perundang-undangan, penafsiran hukum dan a nali sa konsep hukum . Hasil penelitian menunjukkan bahwa tidak diaturnya keberadaan Komisaris dalam Perseroan Terbatas Perseorangan di dalam undang-undang cipta kerja adalah untuk menghindari konflik kewenangan antara Komisaris terhadap Direktur yang sekaligus pemegang saham tunggal. Mustahil proses pengawasan dapat dilakukan oleh Komisaris terhadap direksi sekaligus pemegang saham tunggal yang  memiliki kekuasaan mutlak Sedangkan yang kemudian berwenang untuk mengambil alih tugas dan tanggungjawab  daripada organ Komisaris dalam Perseroan Terbatas Perseorangan adalah Pemegang saham, karena hanya ada satu sosok personal dalam PT Perseorangan yaitu Pemegang Saham Tunggal, yang dirangkapkan jabatannya sekaligus sebagai Direktur.  Organ Komisaris dalam PT Perseorangan wajib diatur dan tetap ada, walaupun dalam proses pelaksanaannya fungsinya hanya sebagai pelengkap, tetapi kekosongan norma dapat dihindari. Perlu pengaturan lebih lanjut untuk menciptakan harmonisasi hukum demi menjamin kepastian hukum.